2020
DOI: 10.1097/mca.0000000000000781
|View full text |Cite
|
Sign up to set email alerts
|

The CHADS-VASc score is a predictor of no-reflow in patients with non-ST-segment elevation myocardial infarction

Abstract: This study was performed to evaluate the relationship between the CHA2DS2-VASc score and no-reflow (NR) phenomena in patients with non-ST-segment elevation myocardial infarction (NSTEMI). A total number of 428 consecutive patients with NSTEMI were assessed for this study. Patients were divided into 2 groups, those with NR, NR(+) (n=84), and those without NR, NR(-) (n=307), according to their post-PCI, no-reflow status. The CHA2DS2-VASc score was significantly higher in the NR(+) group compared to the NR(-) (3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
1
17
0
1
Order By: Relevance
“…30 It also predicts the development of acute stent thrombosis in patients with STEMI following a primary PCI, and no reflow in occluded vessels during ACS. 8,31 Çınar et al showed that the CHA2DS2-VASc score has a predictive value for the development of prosthetic valve thrombosis in patients with mechanical prosthetic valves regardless of the presence of AF. 32 Diabetes mellitus is associated with an increased prevalence and severity of CAD, increased incidence of ACS, and poor outcomes compared with patients without DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 It also predicts the development of acute stent thrombosis in patients with STEMI following a primary PCI, and no reflow in occluded vessels during ACS. 8,31 Çınar et al showed that the CHA2DS2-VASc score has a predictive value for the development of prosthetic valve thrombosis in patients with mechanical prosthetic valves regardless of the presence of AF. 32 Diabetes mellitus is associated with an increased prevalence and severity of CAD, increased incidence of ACS, and poor outcomes compared with patients without DM.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Recent publications have also shown that this score can predict the success of the procedure in patients with ST elevation myocardial infarction (STEMI). 8,9 The present study investigated the utility of the CHA2DS2-VASc risk score as a predictor of TO in patients with NSTEMI.…”
Section: Introductionmentioning
confidence: 99%
“…There are studies supporting the relationship between NR and the CHA 2 DS 2 -Vasc score, which is among these risk scores and is considered to be a prognostic marker for many cardiac conditions. 42–44 In another study, the new CHA 2 DS 2 -VASc-HSF score, which includes hyperlipidemia, smoking, and family history for coronary artery disease in addition to the classical score, was found to be an independent predictor of NR in patients with STEMI treated with pPCI. 17 The NR risk was increased in those with a score ≥2 in the study by İpek et al 45…”
Section: Discussionmentioning
confidence: 99%
“…The CHA2DS2‐VASc score is an easy‐to‐use, reproducible, and effective scoring system that predicts cardioembolic risk in patients with nonvalvular AF 5 . It predicts the development of no reflow in occluded vessels in acute coronary syndrome 10,11 . The pre‐admission CHA2DS2‐VASc score is associated with the 90‐day poor endpoint in ischemic stroke patients with AF 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that this score is associated with higher coronary thrombus burden in patients with acute coronary syndrome 9 . The score is also useful for predicting procedure success in patients with ST elevation myocardial infarction 10,11 …”
Section: Introductionmentioning
confidence: 99%